Chemical-physical characteristics of buffalo (Bubalus bubalis) meat subjected to different aging times - Luz, Patrícia Aparecida Cardoso Da [UNESP]; Jorge, André Mendes [UNESP]; Francisco, Caroline De Lima [UNESP]; Mello, Juliana Lolli Malagoli De [UNESP]; Santos, Carolina Toledo [UNESP]; Andrighetto, Cristiana [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2017)
The aim of this study was to evaluate the effects of different aging times on the meat characteristics from young Murrah buffaloes slaughtered at 20-24 months of age (experiment I; n=10) and Murrah buffalo heifers slaughtered at 32-36 months of age (experiment II; n=10), with the purpose of determining the best aging time to tenderize meat from both experiments. Samples of the longissimus thoracis muscle from buffaloes slaughtered at each age were aged for 7, 14, and 21 days (0±1°C). After this period, analysis of cholesterol, pH, cooking loss, shear force, myofibrillar fragmentation index, meat color, and fatty acid profile was performed. Aging greatly improved the tenderness (p < 0.05) but caused a change in color (p < 0.05), which, even without difference between the treatments for subjective perception of the color (ΔE; p > 0.05), was considered very noticeable to the human eye. Furthermore, aging reduced the polyunsaturated fatty acids (p <0.05) and did not affect the levels of cholesterol (p > 0.05) in the meat of young buffalo and buffalo heifers of advanced age. Based on the evaluated meat characteristics, concludes that seven days of aging are sufficient for older buffalo heifers, but 21 days of aging are required for the younger male group.

Objetivou-se com o estudo avaliar os efeitos de diferentes tempos de maturação sobre as características da carne de búfalos Murrah jovens abatidos com 20-24 meses de idade (experimento I; n=10) e novilhas bubalinas Murrah abatidas com 32-36 meses de idade (experimento II; n=10), com a finalidade de determinar o melhor tempo de maturação para ambos os experimentos. As amostras do músculo longissimus thoracis foram maturadas durante 7, 14 e 21 dias (0 ± 1°C). Após esse período, foi realizada análise de colesterol, pH, perdas de peso por cocção, força de cisalhamento, índice de fragmentação miofibrilar, cor da carne e perfil de ácidos graxos. A maturação melhorou a maciez (p < 0,05), no entanto, modificou a cor da carne (p < 0,05), a qual, mesmo sem diferença entre os tratamentos para percepção subjetiva da cor (ΔE; p > 0,05), foi considerada como muito perceptível ao olho humano. Além disso, a maturação reduziu os ácidos graxos polinsaturados (p < 0,05) e não afetou os níveis de colesterol (p > 0,05) na carne de búfalos jovens e novilhas bubalinas com idade avançada. Com base nas características avaliadas, conclui-se que sete dias de maturação são suficientes para as novilhas bubalinas mais velhas, mas 21 dias de maturação são necessários para o grupo de búfalos mais jovens.
Características químico-físicas da carne bubalina (Bubalus bubalis) submetida a diferentes tempos de maturação
Keywords: cholesterol; fatty acids; longissimus thoracis; Murrah; tenderness; colesterol; ácidos graxos; longissimus thoracis; Murrah, maciez